Measuring Attention in Second Language Reading Using Eye-tracking: The Case of the Noticing Hypothesis - Emrah Dolgunsöz (Journal of Eye Movement Research)
Taking Schmidt’s (1990) noticing hypothesis as point of departure this study aims to measure attention and learning gains during second language (L2) reading by making use of eye-tracking methodology. Relying on Robinson’s hierarchical memory model (1995, 2003), it is hypothesized that vocabulary learning and attention are closely associated. After a vocabulary pre-test, seventy-five learners of English read a standard text individually while their eye movements were being recorded followed by an immediate post-test. The results revealed that learners spent more time on unknown words than they did on familiar ones. Attention and learning gains also positively correlated; fixation values on an unknown word increased its further recognition probability in post-test. Finally, the findings revealed a cut-off point of approximately 450ms as an activation threshold for noticing. Eye-tracking as a technique to measure attention in second language acquisition (SLA) was also discussed.